Faktor-Faktor Penghambat Guru BK Dalam Melaksanakan Program Bimbingan dan Konseling di SMA se-Kota Sungai Penuh - Lita Pratama; Nelyahardi Gutji; Freddy Sarman (Journal on Education, 2023)
The existence of guidance and counseling in schools remains to be met as is expected, for in the school community there are those who are not familiar with the real duties of guidance teachers and counseling. The results of an interview with some guidance counselors, they found that some of the bk services were somehow affected by their performance. The implementation of the program at the school has not reached its intended target because of several obstacles such as education, experience, health conditions, bk teacher competency, tools and infrastructure, regulatory terms, and lack of student participation. The quality of a full-river high school guidance and counseling program, which reveals the quality of the internal factor to which the guidance and counseling programs are conducted at a full-river high school. , and express the quality of external factors to the guidance and counseling program at a full-river high school. The study has been limited to full-river high school guidance and counseling programs, the internal factors that the guidance and counseling teachers have in full-river high schools and the external factors that the guidance and counseling teachers have in full-river high schools.